Perception, knowledge, and attitudes towards molar incisor hypomineralization among Spanish dentists: a cross-sectional study - Clara Serna-Muñoz; Yolanda Martínez-Beneyto; Amparo Pérez-Silva; Andrea Poza-Pascual; Francisco Javier Ibáñez-López; Antonio José Ortiz-Ruiz (BMC, 2020)
Abstract Background Molar incisor hypomineralization (MIH) is a growing health problem, and its treatment is a challenge. The purpose of the present study was to evaluate and compare the perceptions, knowledge, and clinical experiences of MIH in general dental practitioners (GDPs) and paediatric dentists (PDs) in Spain. Methods All dentists belonging to the College of Dentists of the Region of Murcia, in the South-East of Spain, were invited to participate in a cross-sectional survey. They were asked to complete a two-part questionnaire including sociodemographic profiles and knowledge, experience, and perceptions of MIH. Data were analysed using Pearson's chi-square test, Fisher's exact test and Cramer's V test. Results The overall response rate was 18.6% (214/1147). Most respondents were aged 31-40 years (44.86%), with more than 15 years of professional experience (39.72%). They worked mainly in the private sector (84.58%) and were licensed in dentistry (74.30%): 95.45% of PDs had detected an increase in the incidence of MIH in recent years (p <  0.001). Only 23.80% of GDPs claimed to have made a training course on MIH. With respect to the aetiology, chronic medical conditions (p = 0.029) and environmental pollutants (p = 0.008) were the only factors that showed significant between-group differences. Durability (p = 0.009) and remineralization potential (p = 0.018) were the factors where there was a between-group difference in the choice of the restoration material. In the case of post-eruptive fractures and opacities, the preferred material for both groups was resin-modified glass ionomer (RMGIC). However, in incisor lesions, composite was the material of choice for both groups, with significant differences (p = 0.032) in the use of glass ionomer. Most respondents expressed a need for continuing education on MIH. Conclusion Spanish dentists perceived an increase in the incidence of MIH. The material of choice was RMGIC for non-aesthetic sectors and composite for incisors. Dentists believe it is difficult or very difficult to manage MIH, since the long-term success of restorations of MIH lesions is compromised because resin adhesion is not good. Both GDPs and PDs believe they need more training on the aetiology, diagnosis, and treatment of MIH.